Cinacalcet hydrochloride for the treatment of hyperparathyroidism. (August 2014) - Sarav, Menaka; Sprague, Stuart M
<x xml:space="preserve">Abstract</x> Introduction: The identification and cloning of the calcium-sensing receptor (CaSR) in 1993 has enhanced our understanding of calcium metabolism in both health and disease. CaSR, a G protein-coupled receptor, serves as a key signal transduction pathway in a variety of tissues, most notably parathyroid and kidney. The development of agents that activate the CaSR (calcimimetics) has provided for a new approach for the treatment of hyperparathyroidism, especially secondary hyperparathyroidism that is a common complication of chronic kidney disease. Areas covered: This review provides an overview of the CaSR and calcimimetics as well as a detailed discussion about pharmacokinetics, clinical efficacy, safety profile and the clinical indications for the use of <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=cinacalcet&logicalOpe1=OR&field2=articletitle&text2=cinacalcet&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">cinacalcet. Expert opinion: Cinacalcet is presently the only calcimimetic agent approved for the treatment of secondary hyperparathyroidism in dialysis patients. It is also indicated for hypercalcemia due to inoperable parathyroid carcinoma-related parathyroid hormone excess and severe primary hyperparathyroidism in whom surgery is indicated but cannot be performed.